Kahoot! as innovation gamification for examination - Efrilla Niza; Aura Salsabilah Ardian (Curricula: Journal of Curriculum Development, 2022)
Kahoot! is a learning innovation with a gamification method in the form of a platform. This study used a literature review method based on various research results that discuss the implementation of learning using web-based media. The data analysis consists of reading the literature review, summarizing, analyzing, and synthesizing it. The results of this study indicate that in carrying out the learning process, educators need to follow technological developments. By using Kahoot! As a medium for conducting exams or tests, students will get a new and fun experience while doing their exams. This is supported by the website's visual appearance, which uses funny and exciting animations. In addition, in its use, There is no charge, and the application is relatively easy to use. However, the downside of using Kahoot! as a learning media, both educators and students need a good internet network and adequate devices. Kahoot! can be used as an alternative media in learning because of its advantages, but it should also be noted that in its use, Kahoot! Requires a good internet connection and adequate devices.   Abstrak Kahoot! Merupakan sebuah inovasi pembelajaran dengan metode gamifikasi yang berbentuk sebuah platform. Artikel ini menggunakan metode kajian pustaka yang dilakukan pada berbagai hasil penelitian yang membahas mengenai pelaksanaan pembelajaran dengan menggunakan media berbasis web. Proses analisis data terdiri dari membaca tinjauan literatur, merangkum, menganalisis, dan mensitesisnya. Hasil dari kajian ini menunjukan bahwa dalam melakukan proses pembelajaran, pendidik perlu mengikuti perkembangan teknologi. Dengan menggunakan Kahoot! sebagai media untuk melakukan ujian atau tes, peserta didik akan mendapatkan pengalaman yang baru dan menyenangkan saat mengerjakan ujian mereka. Hal tersebut didukung dengan tampilan visual website yang menggunakan animasi-animasi yang lucu dan menarik. Selain itu, dalam penggunaannya, Kahoot! tidak dipungut biaya apapun dan pengaplikasiannya terbilang cukup mudah. Namun, kekurangan dari penggunaan Kahoot! sebagai media pembelajaran adalah baik pendidik maupun peserta didik membutuhkan jaringan internet yang kuat serta perangkat yang cukup memadai. Kahoot! dapat dijadikan sebagai salah satu media alternatif dalam pembelajaran karean kelebihan-kelebihan yang ditawarkannya, namun perlu diperhatikan juga, dalam penggunaannya, Kahoot! memerlukan koneksi internet yang kuat dan perangkat yang memadai. Kata Kunci: Evaluasi pembelajaran; gamifikasi; Kahoot!; kuis